2020
DOI: 10.18231/2394-6792.2018.0020
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of haematological parameters and C-reactive protein in early detection of neonatal septicaemia in developing countries

Abstract: Introduction: Septicaemia is one of the major causes of mortality and morbidity during the neonatal period especially in developing countries. Early diagnosis of neonatal sepsis is a diagnostic problem due to non-specific clinical features. Blood culture is the gold standard, but it takes several days and is expensive. Hence there is a critical need for laboratory tests that aid in the rapid diagnosis of neonatal sepsis. Aims and Objectives: To measure the role of Haematological Scoring System and C-reactive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 12 publications
5
0
0
Order By: Relevance
“…In this study, TLC had a sensitivity of 35.3%, specificity of 77.1%, NPV of 85.3%, and a PPV of 24%. These results are comparable with studies performed by Nayak et al 12 and Makadia and Shah. 13 In this study, HSS had a sensitivity of 64.7%, specificity of 15.7%, NPV of 68.4%, and a PPV of 13.6%.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, TLC had a sensitivity of 35.3%, specificity of 77.1%, NPV of 85.3%, and a PPV of 24%. These results are comparable with studies performed by Nayak et al 12 and Makadia and Shah. 13 In this study, HSS had a sensitivity of 64.7%, specificity of 15.7%, NPV of 68.4%, and a PPV of 13.6%.…”
Section: Discussionsupporting
confidence: 92%
“…These results are comparable with studies performed by Nayak et al 12 and Sundarapandian et al 16 In addition, a few other studies showed that nRBC count is also increased in neonatal sepsis. 12,17 nRBC count in a term neonate is said to increase in hypoxia, severe anemia, acute stress, and sepsis. In neonatal sepsis, nRBC count is increased due to release of cytokines and is independent of hypoxia.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations